Elevated Ca 19-9 Levels in Patient With Cholecystitis - Şahin, Mehmet; Cüre, Erkan; İşler, Mehmet; Barut, İbrahim (Fırat University, 2007)
Although CA 19-9 is a tumour marker, high levels of CA 19-9 have also been reported in benign conditions such as acute cholangitis or pancreatitis. We present here a 56-year-old woman with complicated cholecystitis due to gallstone and elevated serum CA19-9 levels. After cholecystectomy procedure CA19-9 level returned to normal. The level of CA 19-9 should never be regarded as a gold standard but rather as a helpful indicator when searching pancreatic and biliary malignancies. ©2007, Firat University, Medical Faculty

CA 19-9 bir tumör belirleyicisi olarak kullanılmasına rağmen akut kolanjit ve pankreatit gibi benign durumlarda da yüksek düzeyleri bildirilmiştir. Bu vakada 59 yaşında safra taşına bağlı komplike olmuş bir kolesistit ile birlikte yükselmiş CA 19-9 düzeyine sahip bir hastamızı sunuyoruz. CA 19-9 düzeyi kolesistektomi sonrasında normale döndü. CA 19-9 düzeyi altın standart bir test olmamakla birlikte, pankreas ve safra kesesi malignitelerini araştırmada yardımcı bir test olarak kabul edilmelidir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Kolesistitli Bir Olguda Yüksek Ca 19-9 Seviyesi